2023
DOI: 10.1515/biol-2022-0585
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal HBV-DNA for diagnosis and treatment monitoring of chronic hepatitis B

Abstract: This study examined exosomal hepatitis B virus (HBV)-DNA levels in chronic HBV infection (CHB). Patients were grouped according to the European Association for the Study of the Liver classification (1: HBV-DNA-positive CHB, normal alanine aminotransferase [ALT]; 2: HBV-DNA-positive CHB, elevated ALT; 3: HBV-DNA-negative HBeAb-positive CHB, normal ALT; 4: HBV-DNA-positive HBeAg-negative HBeAb-positive CHB, elevated ALT; 5: HBV-DNA-negative, HBcAb-positive; 6: HBV-negative, normal ALT). Exosomes were isolated, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Patients who test negative for serum HBV-DNA but have a strong suspicion of HBV infection may benefit from using exosomal HBV-DNA. Not Taking The size and quantity of serum exosomes were measured by NTA using a particle size analyzer (Particle Metrix GmbH, Ammersee, Germany) [ 141 ]. As important clinical markers, serum HBV-DNA and ALT are often utilized to identify and assess CHB patients.…”
Section: The Role Of Exosomes In Viral Disease Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who test negative for serum HBV-DNA but have a strong suspicion of HBV infection may benefit from using exosomal HBV-DNA. Not Taking The size and quantity of serum exosomes were measured by NTA using a particle size analyzer (Particle Metrix GmbH, Ammersee, Germany) [ 141 ]. As important clinical markers, serum HBV-DNA and ALT are often utilized to identify and assess CHB patients.…”
Section: The Role Of Exosomes In Viral Disease Diagnosismentioning
confidence: 99%
“…It should be mentioned that no relationship was found between the amounts of HBV-DNA in serum and exosomes and ALT, a crucial biochemical marker of liver impairment. Thus, tracking the amount of HBV-DNA in exosomes may help select therapy to stop the illness from developing into LC and cancer and immediately and adequately represent the onset and progression of the disease [ 141 144 ].…”
Section: The Role Of Exosomes In Viral Disease Diagnosismentioning
confidence: 99%
“… 239 When a patient's serum HBV‐DNA is negative, exosomal HBV‐DNA accurately reflects the level of HBV replication in the body and allows for tracking of treatment. 240 Characterization of Mycobacterium exocytosis RNA from infected macrophages reveals unique mRNA fingerprints and preferential exocytosis markers for host‐mRNA–miRNA and TB RNA in Mycobacterium tuberculosis infection. 241 Distinctive expression patterns of exosomal miRNAs (miR‐148a‐3p, miR‐150‐5p, and miR‐451a) in pleural effusions from benign wounds and tuberculosis could serve as potential biomarkers for tuberculosis pathology.…”
Section: Exosome Biomarkersmentioning
confidence: 99%
“…DNA mutations are involved in many tumor advantages, most notably resistance to therapies, and represent a potential tumor biomarker [71]. Detecting exosomal DNA in clinical samples is receiving a large consensus in cancer patients [75][76][77][78] and other diseases, including viral-related pathological conditions [79]. In addition, recent reports have shown that exosomes purified and concentrated from body fluids, such as ascites, may express high levels of protein glycosylation [80].…”
Section: Exosomes Deliver Nucleic Acidsmentioning
confidence: 99%